'Finishing up' on country: challenges and compromises. Issue 9 (16th September 2016) - Waran, E.; O'Connor, N.; Zubair, M. Y.; May, P.
Abstract : A core consideration in the care of Indigenous patients at the end of life is their place of death. Dying in community can be of paramount importance to Indigenous people. This paper reports the experiences of the Top End Palliative Care Service with respect to the barriers and solutions in the return of Indigenous patients to community for end‐of‐life care. These barriers include not only those associated with the significant distances and remoteness in the Northern Territory but, also, spiritual and cultural factors, which often influence healthcare delivery.